EXECUTION MECHANISM OF MORTGAGE RIGHTS USING EXECUTORIAL TITLE IN SHARIA BANKING IS WHOSE AUTHORITY? - Afif Noor; Bagas Heradhyaksa (Diponegoro Law Review, 2020)
Mortgage Right is a guaranteed right to land that is attached to the debt process. The authority to execute the guarantee of Liability on Sharia banks is an important matter to be discussed in the study of business law or commercial law as an effort to return loans that have been given by creditors (sharia banks) to debtors (customers) on financing problems or breach of contract. The Guarantee of Mortgage will not have meaning if the guarantee cannot be executed. The significance of this study is to know the mechanism of request for execution of guarantee of mortgage rights at a sharia bank after the decision of the Constitutional Court No. 93/PUU-X/2012. The research methodology used in this article is the research library. This article analyzes the laws related to the mechanism of execution of mortgage rights in sharia banks. Finally, this research found that the execution of  mortgage righst in Islamic banks is the authority of the Religious Court. The mechanism for requesting the execution of a mortgage guarantee at a sharia bank is also the same as the mechanism for requesting mortgage rights at a district court.